1992
DOI: 10.3109/01902149209031703
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Action of Tetrandrine on Macrophage Production of Interleukin-1 (IL-l)-Like Activity and Thymocyte Proliferation

Abstract: Tetrandrine is a bisbenzylisoquinoline alkaloid which has been shown to exhibit antifibrotic activity against silicosis. Tetrandrine is characterized by its strong binding to alveolar macrophages and inhibition of particle-induced respiratory burst activity in these phagocytes. In contrast, tubocurine and tubocurarine are structurally similar to tetrandrine but exhibit little effect on fibrosis or activation of alveolar macrophages. The objective of the present study was to test the effect of tetrandrine on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The interleukin-1 (IL-1) activity of BAL cell-conditioned media was determined according to a previously described method (Kang et al, 1992;Ma et al, 1999). Thymocytes were obtained from male CD-1 mice (6-10 wk of age) and suspended in RPMI-1640 medium supplemented with 2 mM glutamine, 100 U/ml penicillin, 100 µg/ml streptomycin, 10% heatinactivated fetal bovine serum, and 2 × 10 -5 M mercaptoethanol.…”
Section: Il-1 Determinationmentioning
confidence: 99%
“…The interleukin-1 (IL-1) activity of BAL cell-conditioned media was determined according to a previously described method (Kang et al, 1992;Ma et al, 1999). Thymocytes were obtained from male CD-1 mice (6-10 wk of age) and suspended in RPMI-1640 medium supplemented with 2 mM glutamine, 100 U/ml penicillin, 100 µg/ml streptomycin, 10% heatinactivated fetal bovine serum, and 2 × 10 -5 M mercaptoethanol.…”
Section: Il-1 Determinationmentioning
confidence: 99%
“…Tet has been shown to suppress the production and activity of human monocyte IL-1 in vitro (10)(11)(12). It is hypothesized that the ocular anti-inflammatory action of Tet may be related to the inhibition of IL-1.…”
mentioning
confidence: 99%
“…Many iNOS inhibitors have been reported to be beneficial in endotoxemic conditions. Previously, we reported that isoquinoline analogs inhibit iNOS mRNA and protein expression in rat aorta and RAW 264.7 cells, induced by LPS and cytokines (Tainlin et al, 1982;Kang et al, 1992;Chen et al, 1997). Therefore, isoquinoline alkaloids are of special interest for their pharmacological actions on inflammation and related disorders.…”
mentioning
confidence: 99%